Impact Closure of Prostitution Guise Ritual Practice Pilgrimage in Mountain Kemukus, Sragen, Central Java - Nur Cholid; Maas Shobirin (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
The phenomenon of ritual pilgrimage at Mount Kemukus is very disturbing society as a ritual pilgrimage undertaken against the teachings of Islam. In addition to making sexual relations as an essential prerequisite in achieving the intent (wealthormate), in the selocations is also provided to provide sex workers to servetheguests (pilgrims) who visited the tomb of Prince Samudro. Yet, as the criticism of society, prostitution is finally issued by the district government, Sragen. This study aimed to describe the impact of what is experienced by residents of the surrounding mountains kemukus post-closure prostitution in the aspect of religion, social and economic and socio-cultural conditions of the people in Mount kemukus. This research is a field research. The technique of collecting data is interviews, observation and documentation. Thus, the results of data are analyzed by using qualitative data analysis which refers to the Miles and Huberman (reduction, display, and conclusion verification). The results of research showed that the condition of the people there are much believed was right about the existence of the mythical prince and his Samudro rituals. Furthermore, as a result of the closure of the mountain cubeb impact in several areas of religious, social, economic, especially local residents who make revenue decline. Keywords: Prostitution, ritual, pilgrimage